Block copolymerization of methylmethacrylate via ATRP method using a macroinitiator produced by ring opening polymerization: Characterization, dielectric properties, and a kinetic investigation - Torgut, Gulben; Demirelli, Kadir (Taylor & Francis Inc, 2016)
Poly(2-(3-methyl-3-phenylcyclobutyloxirane-co-E-caprolactone) [P(PCBO-co-E-CL)] was synthesized by ring opening polymerization (ROP) of 2-(3-methyl-3-phenylcyclobutyloxirane and E-caprolactone (E-CL) using benzyl alcohol as the initiator and Sn(Oc)(2) as the catalyst. To produce a macroinitiator from copolymer with hydroxyl end group was carried out reaction of acylation with choloroacetyl chloride. The molecular structures of copolymers were confirmed by FT-IR, H-1-NMR spectroscopies and gel permeation chromatography (GPC). A kinetic series of methyl methacrylate (MMA) via ATRP method were studied in the presence of this macroinitiator and using CuBr/2,2-bipyridine (bpy) as catalyst at 110 degrees C. The kinetic study showed that the polymerization proceeded in a controlled way up to high conversions and the number-average molecular weight (M-n) increased depending on time. The thermal properties of copolymers were evaluated by TGA and DSC measurements. The temperature and frequency dependence of dielectric constant (?) and dielectric loss factor (E) of P[(PCBO-co-E-CL)-b-PMMA] and that of doped with different concentration of EuCl3 were investigated between the frequency of 100-2000Hz and temperature range (300-430K). Also, the ac conductivity has been measured to see the effect of frequency and temperature.
Keywords: Ring opening polymerization; ATRP; dielectric permittivity; conductivity; poly(E-caprolactone)